Quantifying environmental impacts of the Climate Smart Agricultural practices tested in two Ethiopian Woredas - Damerau, Kerstin (2021)
Ethiopian smallholders are increasingly threatened by climate change and ongoing land degradation. Aiming at adapting to locally varying environmental and socio-economic challenges and improving the sustainability and resilience of agricultural livelihoods, a set of locally appropriate climate-smart agriculture (CSA) practices have been tested by farmers on a voluntary basis between 2019 and 2021 in two Climate-Smart Landscapes as part of the IFAD-EU project “Building livelihoods and resilience to climate change in East & West Africa”. To address the dual challenges of environmental change and declining food security we aimed at assessing and quantifying environmental impacts of CSA practices tested in this project. To do so, we calculated yield differences of major crops grown by both adopting and non-adopting farms as basis for assessing associated deviations in land use, water use efficiency, overall (and where applicable irrigation) water use as well as greenhouse gas emissions. After one year, relative differences in median crop yields between specific practices and practice combinations showed very mixed results in both regions. There was, however, a slight trend of combined practices performing somewhat better than single practices. This finding is congruent with previous reports, as multi-year adaptation periods might be required in order to observe patterns in farm performance and health. Our survey-based results further underline the urgent need for more quantitative rather than empirical assessment and documentation of various environmental and productivity indicators. Finally, we provide a basis for discussing how resulting relative changes in environmental impacts of CSA can potentially be transferred and applied to comparable agricultural landscapes in other parts of sub-Saharan Africa.